TRANSAKSI OBLIGASI SYARIAH (TINJAUAN TRANSAKSI OBLIGASI MENURUT PRINSIP-PRINSIP SYARIAH) - Maisarah Leli (JURIS (Jurnal Ilmiah Syariah), 2017)
One model of economic development in the era of globalization is the rapid development of capital markets in a country. Capital market is one form of alternative fundings for business development and possesses strategic place in the framework of national development, and investment facilities for investors who have excess funds. Many investors capitalize on the capital market to conduct investment portfolios of interest, and among the options used are bonds. Indonesia which applies dual system banking system realizes that instead of transactions originating from Conventional Financial Institutions, there are also ones in Sharia Financial Institutions. Basically, the the principle differences between the conventional economic system with the syari'ah economic system is the prohibition of transactions that use usury, which has been used by the Bank / Conventional Financial Institution. Syari'ah bonds are belived to be prospective, but their development is still hampered in technical problems and public understanding of this transaction.  Less effective and efficient socialization and less familiarity of the people toward the profit and loss sharing transactions, or other sharia principles make people still think that Islamic bonds are the same as those of conventional. As a result the think that interest is identical weth profit sharing.